1976
DOI: 10.1136/hrt.38.2.180
|View full text |Cite
|
Sign up to set email alerts
|

Length of main left coronary artery in relation to atherosclerosis of its branches. A coronary arteriographic study.

Abstract: The relation between the length of the main left coronary artery and the presence of atherosclerosis in its branches or the presence of complete left bundle-branch block was studied by selective coronary arteriography in 43 persons.The length of the main left coronary artery wasfound to be significantly shorter in patients with coronary atherosclerosis than in subjects without angiographic evidence of coronary artery disease. In patients with electrocardiographic evidence of complete left bundle-branch block,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
20
1
4

Year Published

1981
1981
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 12 publications
5
20
1
4
Order By: Relevance
“…The mean length of the left coronary artery was variously reported by different authors. Lewis et al [15] reported a length of 12.8 mm, Fox et al [1] 9.5 mm, Kronzon et al [18] 10.4 mm, and Gazetopoulos et al [7,12] found it to be 12.4 mm. Although "short" MT and "long" MT were considered as variants in the length of the left coronary artery, [19] there is no commonly agreed upon definition of a short and long MT.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The mean length of the left coronary artery was variously reported by different authors. Lewis et al [15] reported a length of 12.8 mm, Fox et al [1] 9.5 mm, Kronzon et al [18] 10.4 mm, and Gazetopoulos et al [7,12] found it to be 12.4 mm. Although "short" MT and "long" MT were considered as variants in the length of the left coronary artery, [19] there is no commonly agreed upon definition of a short and long MT.…”
Section: Discussionmentioning
confidence: 99%
“…Gazetopoulos et al, [7,12] Reig and Petit [5] suggest that there is a positive correlation between the length of the trunk and the bifurcation angle, with the longest trunk has the largest angle. Although our results are similar to those of this study we did not found this relation statistically meaningful.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations